Familial colorectal cancer risk may be lower than previously thought: A Danish cohort study. Issue 5 (October 2015) - Lautrup, Charlotte K.; Mikkelsen, Ellen M.; Lash, Timothy L.; Katballe, Niels; Sunde, Lone
Highlights We investigated familial colorectal cancer risk. Monogenetic cancer syndromes were systematically excluded. First degree relatives to colorectal cancer patients have a 2-fold increased risk of the disease. The risk is not further increased in first degree relatives to patients diagnosed young. Having multiple affected relatives does not give a further increase in the risk.